Process flow for work breakdown structure in plannning and scheduling : a comparative case study - Nurulzanna, Idris (2014)
Developing a work breakdown structure is an important step during the initial phase of the project that once the basic scope have been identified, initial work breakdown structure can be created with a limited scope of information. A work breakdown structure is the basis for planning and managing the key areas within a project. If work breakdown structure is not designed properly, it can have an impact on the whole project as work breakdown structure serves as the basis of planning. The impact for not proper of the work breakdown structure is not clear work assignments and goals difficult to achieve. Experienced project managers know that there are many things wrong or not right in the project no matter how he managed the planning and execution of their work. Unfortunately for inexperienced planners, they can not anticipate what will happen if they do not prepare properly planning. Proper planning should be done to avoid problems that cannot be expected in the future. If not, many problems will arise, especially during construction. Thus, planner must understand and know how to develop a work breakdown structure correctly. For inexperienced planners, there may be some problems in the planning process. In general, an inexperienced planner has problems in the initial stage. He could not identify which one should be done first. Therefore, this study was come out to study the process flow of work breakdown structure during the planning stage. The objectives of this study are to define the process flow of work breakdown structure based on case study, to identify the similarity on process flow of work breakdown structure among case study and to suggest the suitable process flow of work breakdown structure that can be use for inexperienced planner. In this study, data collection is carried out by interviews. Three of the contractors involved in the planning process will be selected, for this case study. Then, an interview with three project managers will be conducted. As a result, three case studies has similar process flow but different in the sequence only. Difference sequence based on their experience factor. This research hopes to contribute to the planning of inexperience, especially in developing work breakdown structure in the right way.